(untitled) (Research, Society and Development, 2020)
This article has the general goal of presenting a critique of the main techniques for preparation of academic papers, as well as indicating exercises for their better apprehension, resulting in a specific educational object. It is argued that students, in doing so, take ownership of this “practical knowledge” while acquiring the ability to organize their studies in a satisfactory manner, archiving their textual production, building a theoretical framework, developing at the intellectual level, and thus, constructing critical and autonomous thinking in relation to knowledge. Therefore, it is believed that students should be able to produce a critical memory of the contents of the subjects in undergraduate courses, which is crucial in the preparation of an Undergraduate Thesis (TCC) and in professional life as a whole, as such knowledge is required, as well as in the continuity of academic training in graduate school. Finally, it is concluded that the appropriation of such knowledge is at the core of scientific education, thereby enabling students to perform academic research and knowledge production while ensuring student autonomy.